Catalytic Enantioselective Friedel–Crafts Reactions of Arenes Enabled by Iranium/Irenium-Ion-Triggered Electrophilic Functionalization - Zhang, Yuanyuan; Ding, Shuai; Meng, Limin; Tao, Chuanzhou; Wang, Huiyan; Xu, Song (Synlett, 2025)
The catalytic asymmetric Friedel–Crafts reactions of (hetero)arenes represent a cornerstone in synthetic chemistry due to their ability to efficiently incorporate aromatic rings into complex molecular architectures. This account presents a comprehensive overview of recent advancements in the catalytic enantioselective Friedel–Crafts reactions of (hetero)arenes, with a particular focus on reactions that facilitate the introduction of aromatic rings into multiple C–C bonds via iranium/irenium-ion-triggered electrophilic processes. We examine in detail the strategies and methodologies employed to achieve stereoselective incorporation of (hetero)arenes into unsaturated C–C bonds, highlighting the construction of diverse structural scaffolds. Additionally, this account showcases the broad range of applications of this powerful transformation in organic synthesis.1 Introduction2 Catalytic Enantioselective Friedel–Crafts Reactions via Thiiranium/Thiirenium Ions2.1 Arylthiiranium/Arylthiirenium-Ion-Triggered Catalytic Enantioselective Friedel–Crafts Reactions2.2 Trifluoromethylthiiranium/Trifluoromethylthiirenium-Ion-Triggered Catalytic Enantioselective Friedel–Crafts Reactions3 Catalytic Enantioselective Friedel–Crafts Reactions via Haliranium Ions3.1 Chloriranium-Ion-Triggered Catalytic Enantioselective Friedel–Crafts Reactions3.2 Bromiranium-Ion-Triggered Catalytic Enantioselective Friedel–Crafts Reactions3.3 Iodiranium-Ion-Triggered Catalytic Asymmetric Oxidative Arylation of Alkenes4 Conclusion and Outlook
Keywords: catalytic asymmetric synthesis; Friedel–Crafts reaction; iranium/irenium ions; unsaturated bonds; electrophilic addition